Associations between need-supportive teaching and student and teacher emotions: a mixed-methods investigation - Jiang Jingwen W; Benita Moti; Steffgen Sarah Teresa; Haerens Leen; Lai Ka Wing Karen (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This study investigated associations between need-supportive teaching and student and teacher emotions using mixed methods. Quantitative data were gathered from the self-reports of 326 lower-secondary school students from 22 classes in Finland. Qualitative data were obtained from semi-structured interviews with four teachers. The student ratings revealed considerable between-class variances in perceived teacher emotions. The teacher interviews confirmed that teachers experienced different emotions in different classes. No significant associations between negative emotions and need support were found based on student ratings, while negative emotions were found to be connected with need support based on teacher interviews. The overall results, which combined structural equation modeling of student ratings and thematic analysis of teacher interviews, suggested the existence of reciprocal relationships between need-supportive teaching and the emotions of students and teachers. Implications for intervention research on teaching practices and teacher education are also provided.